Paleoseismological evidence of Holocene activity of the Los Tollos Fault (Murcia, SE Spain): A lately formed Quaternary tectonic feature of the Eastern Betic Shear Zone - Insua-Arévalo, J. M.; García-Mayordomo, J.; Salazar, A.; Rodríguez-Escudero, E.; Martín-Banda, R.; Álvarez-Gómez, J A.; Canora, C.; Martínez-Díaz, J. J. (Journal of Iberian Geology, 2015)
The Los Tollos Fault is a recent and important feature of the Eastern Betic Shear Zone, one of the major tectonic structures in South Iberia accommodating the convergence between Nubian and Eurasian plates in the western Mediterranean. The Los Tollos Fault became active by the end of Middle Pleistocene introducing some paleogeographical modifications. Previously mapped as a secondary normal fault related to the Carrascoy Fault, recent research evidences that the Los Tollos Fault is an independent Holocene active left-lateral reverse fault extending for at least 15 km. Data analysis from 4 trenches dug across the fault has revealed the occurrence of at least two paleo-earthquake events during the Holocene. The most recent event is dated between 2,740 and 2,140 yr BP (8th to 2nd centuries BC). The size of the paleoevents is calculated to be Mw 6.3 – 6.6 following empirical regressions on surface rupture length. The recurrence interval is estimated to be between 2,200-6,860 years, fitting a slip rate for the fault between 0.12 and 0.17 mm/yr. Such parameters highlight the Los Tollos Fault as a tectonic structure with a considerable activity located relatively close to densely populated areas. These seismogenic parameters should be considered in future reassessments of the seismic hazard of the region.